Risk of tremor and impairment from tremor in relatives of patients with essential tremor: A community-based family study - Louis, Elan D.; Ford, Blair; Frucht, Steven; Barnes, Livia F.; X-Tang, Ming; Ottman, Ruth (Annals of neurology, 2001)
Essential tremor (ET) is a common condition that is present in as many as 23% of elderly individuals. Our objective was to determine the risk of ET and to study the impairment resulting from ET among relatives of ET cases compared to relatives of controls. ET cases and matched controls from the Washington Heights‐Inwood community, New York, and their first‐ and second‐degree relatives underwent a standardized tremor examination. The risk of having ET in relatives of cases vs relatives of controls was compared using Cox proportional hazards models. Five hundred ninety‐one subjects were examined (59 ET cases, 72 controls, 234 case relatives, and 226 control relatives). ET was present in 25 (22.5%) of the 111 first‐degree relatives of cases compared to 6 (5.6%) of 107 first‐degree relatives of controls [relative risk (RR) = 4.67, 95% confidence interval (CI) = 1.90–11.49, p = 0.0008]. RRs were higher in relatives of cases with onset ≤50 years than in those with later onset (RR = 10.38 vs 4.82). Sixteen (64%) of twenty‐five affected first‐degree case relatives exhibited moderate tremor while performing tasks such as writing, drinking, or pouring. Relatives of ET patients are five times more likely to develop the disease than are members of the population and ten times more likely if the proband's tremor began at an early age. The majority of the affected relatives can expect to experience impairment resulting from tremor.